2019
DOI: 10.1038/s41433-019-0545-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in utilisation of low vision assistive products

Abstract: Aim To understand the barriers in utilisation of low vision assistive products (LVAPs) from the perspective of patients with low vision. Methods Patients referred to low vision clinic in a tertiary eye care hospital in India who were prescribed LVAPs but were un-willing to accept the products were interviewed using questionnaires. Data pertaining to the age, diagnosis, gender, occupation, preferred LVAPs, patient's perception of vision loss and the primary reason for non-acceptance of LVAPs were analysed.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
2
27
2
2
Order By: Relevance
“…Interestingly, LVS patients were more likely to utilise low vision aids, which may indicate better access to specialised, for‐profit, low vision optometrists and other non‐profit LVS that also prescribe low vision aids, or, increasing collaboration between these companies and LVS. This differs from previous studies that suggested LVS patients experience a barrier to obtaining low vision aids 42 . However, this referral pathway is in complete agreement with the Dutch referral guidelines.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Interestingly, LVS patients were more likely to utilise low vision aids, which may indicate better access to specialised, for‐profit, low vision optometrists and other non‐profit LVS that also prescribe low vision aids, or, increasing collaboration between these companies and LVS. This differs from previous studies that suggested LVS patients experience a barrier to obtaining low vision aids 42 . However, this referral pathway is in complete agreement with the Dutch referral guidelines.…”
Section: Discussioncontrasting
confidence: 61%
“…Results of generalised estimating equations (GEE) analysis: The effects of time (year) on patient characteristics barrier to obtaining low vision aids 42. However, this referral pathway is in complete agreement with the Dutch referral guidelines.Moreover, LVS patients were mainly older adults over 65 years of age, female, had low or middle SES, macular related diseases and lived in urban areas within 20 km of LVS locations.…”
mentioning
confidence: 67%
“…Desde que la RP se manifiesta, las personas se ven condicionadas por los procesos de adaptación de su self a la nueva realidad generada por la patología. Además, también se tienen que enfrentar a la estigmatización, al tratamiento diferencial y la negación de oportunidades (Bulk et al, 2020;Sivakumar et al, 2020). Estos procesos pueden ser producidos por los propios afectados o por los demás.…”
Section: Discussionunclassified
“…The use of assistive aids has been shown to result in the negative evaluation of intelligence, achievement, and appearance of people with disabilities by drawing negative attention to the user as an “unordinary person” and a belief that person may be a liability rather than an asset [ 50 , 51 ]. A recent study found that one of the most common causes of non-acceptance of assistive devices among people with visual impairments was social stigma and the fear of loss of employment, especially in working-age adults [ 52 ]. Similarly, another study exploring employment outcomes among adults with Retinitis Pigmentosa found that use of a cane or guide dog significantly reduced the odds of being employed among study participants [ 53 ].…”
Section: Discussionmentioning
confidence: 99%